2015
DOI: 10.1007/s13204-015-0455-1
|View full text |Cite
|
Sign up to set email alerts
|

Facile approach to synthesize magnesium oxide nanoparticles by using Clitoria ternatea—characterization and in vitro antioxidant studies

Abstract: Facile approach to synthesize the metal oxide nanoparticles is getting an increased attention in various biomedical applications such as, to treat antibiotic resistant diseases. Magnesium oxide nanoparticles (MgOÁNPs) were synthesized by using Clitoria ternatea as the stabilizer in a green synthesis approach. The preliminary screening of MgOÁNPs in the presence of C. ternatea extract was observed by UV-visible spectrophotometer. X-ray diffraction (XRD) pattern have proved the crystalline nature of the MgOÁNPs;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
41
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 123 publications
(47 citation statements)
references
References 36 publications
6
41
0
Order By: Relevance
“…141 Nanosized Mg and its alloys have been reported to exhibit antiinflammatory and antioxidant activity. 142 A few common mechanisms, including ROS generation, have been proposed …”
Section: Magnesium Nanomaterialsmentioning
confidence: 99%
“…141 Nanosized Mg and its alloys have been reported to exhibit antiinflammatory and antioxidant activity. 142 A few common mechanisms, including ROS generation, have been proposed …”
Section: Magnesium Nanomaterialsmentioning
confidence: 99%
“…Among various metal oxides, magnesium oxide (MgO) is a functional semiconductor that has multiple applications in drug delivery, pharmaceutics, optoelectronics, cell signaling, and imaging because of its potent antimicrobial and antioxidant properties. 12,13 Previous studies have examined the protective effects of MgO NPs on oxidative stress parameters induced by malathion and chlorpyrifos, the widely used OP. 13,14 It was observed that malathion-induced cardiac cell toxicity is improved by administration of Mg as a result of increasing cardiac adenosine triphosphate (ATP) through active transport of Mg inside the cells.…”
Section: Introductionmentioning
confidence: 99%
“…[34][35][36] In this context, successive phytosynthetic routes have been investigated and reported, 37,38,[42][43][44][45][46] and have many advantages in terms of reduced toxicity, and the simplicity of method over the chemical synthesis approach. 39,40,83 In the present study, bio-templated mixed metal oxides have been investigated as a facile, greener nanomaterial with enhanced surface properties to replace chemically synthesized material. Thus, the focus of the present study is the synthesis of ZnO/Mn 3 O 4 nano-material using leaf extracts of the Olea ferruginea Royle (OFR) plant taken from Azad Jammu Kashmir, Pakistan.…”
Section: Introductionmentioning
confidence: 99%